Digital energy systems and fundamental rights: smart metering in the EU and three CEE countries - Biró, Zsófia (Journal of comparative politics, 2026)
Article provides a comparative legal analysis of smart metering regulations in Hungary, Slovenia, and Croatia, assessing how national frameworks align with EU objectives on energy efficiency, consumer rights, and data protection. While Hungary applies a pilot based, cautious rollout with unclear long-term goals, Slovenia offers detailed technical standards and data categories but shows enforcement gaps. Croatia adopts a forward-looking, consumer oriented and cybersecurity-aware model, yet requires refinement in definitions and data retention rules. The article concludes that an optimal regulatory model could combine Hungary’s flexibility, Slovenia’s data precision, and Croatia’s consumer protection. However, effectiveness depends on full alignment with the GDPR and the establishment of clear, enforceable rights for data subjects. The article also proposes two follow-up directions: (1) developing a practical guide for consumers on their rights regarding smart meters, and (2) exploring competition law implications related to exclusive access to consumer data in liberalized energy markets. Without harmonized EU-level data governance, smart metering may risk reinforcing regulatory inconsistencies and market imbalance.
Keywords: consumer rights; data protection; energetska regulativa; energy regulation; kakovost zakonodaje; legislative quality; pametno merjenje; pravice potrošnikov; smart metering; varstvo podatkov